Substantial characteristics of the tourist complex as an object of the state policy - Barna, Marta; Iablon, Volodymyr (Journal of Education, Health and Sport, 2024)
The relevance of the problem of improving the theoretical and methodological foundations of tourism as a complex of the national economy lies in the fact that this sector of the economy has every reason to become one of the priority and promising branches of the national economy of Ukraine. The grounds for this conclusion are good natural and climatic conditions and the presence of a wide variety of tourist resources, namely natural-recreational, historical-cultural and socio-economic. Ukraine is characterized not only by a large number of destinations, but also by itself, in general, it can be considered as a single large complex tourist destination.The purpose of the study is to improve the conceptual provisions and substantive characteristics of the tourist complex as an object of the state policy.During the study, the methods of logical generalization (to determine the conceptual provisions of the tourist sector of the economy), grouping (to identify the environment of the tourist sector), analysis and synthesis (to ensure a systematic approach in the formation of the state policy for regulating the development of the tourist sector) were used.The applied value of the research results concerns the identification of the decomposition of the tourist complex of the national economy.The scientific novelty of the research results lies in the further development of the methodological and applied principles of tourism as (1) an industry, (2) a type of economic activity, (3) a sector, (4) a complex of the national economy.